Effective management communication framework for Malaysian Takaful operators in achieving its objectives as social based institutions - Harun, Hafiza; Hassan, Rusni (2017)
Purpose - This paper proposes framework for effective management communication to ensure its effectiveness in according to Malaysian Takaful Operators’ objective. As obviously noted, Malaysian Takaful operations have gone through its convincing and promising development for more than 33 years. In parallel with the enhancement of products, services and regulatory aspects, assessing the roles and functions played by key functionary organs for Islamic Financial Institutions (IFIs) are highly regarded. This is important to ensure that the effectiveness and efficiency had been achieved as required by the compliance requirement. Being one of the key components in governance structure, management is considered as the “main driver” for any institution to gear up its movement. The management of Malaysian TOs are accountable to ensure the overall compliance to Shariah which is known as holistic culture throughout the organization. In supporting as well as enhancing this accountability, strategic monitoring by the respective regulatory bodies on management communication for Malaysian TOs needs to be emphasized accordingly. This paper is started with the discussion on literature review topics such as effective communication, theories related to management, functions of management in the Shariah Governance Framework (SGF) and Islamic Financial Services Act (IFSA), roles of Takaful operators as social based institutions. The framework deliberated in this paper discusses on the recommended components for internal communication in assessing the management of Malaysian TOs. Methodology - This paper proposes a framework of management communication for Malaysian Takaful Operators (TOs). In assessing management communication for eleven (11) Malaysian TOs, there are some important aspects are examined. Those aspects are Shariah Compliance Operating Principles and Social Aspects which represented by TOs through its role in commercial as well as social contributions as explained in the Literature Review Section.Findings - In managing IFI requires management to be well verse in Shariah requirements and applicable laws. Additionally, TO with its roles in serving the welfare of community, also requires management to ensure the other components such as Maqasid Al-Shariah and charity are being fulfilled.The framework deliberated in this paper discusses on the recommended components for internal communication in assessing the management dedicated specifically for Malaysian TOs.